Development of DBUS-Based E-Modules Using Book-Creators to Improve Students' Critical Thinking Skills - Rahayu, Rina; Ismawati, Riva; Winarto, Winarto (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 8 No 1 (2024): JIPVA (Jurnal Pendidikan IPA Veteran)DO - 10.31331/jipva.v8i1.2854, 2024)
Students' critical thinking skills are needed in everyday life because real-life problems will be more complicated and complex. DBUS (Discovery-Based Unity of Sciences) is one of the well-known learning models that can accommodate hands-on experience. It can gain the strength to accept, store, and apply the concepts that students have learned. This research aims to develop an e-module based on the structure and function of animals based on DBUS using a book creator to develop the critical thinking skills of students with valid and qualified criteria. This study is a study of the development of the ADDIE model. Validation results for material and media obtained a high rating category and values of 0.80 and 0.85. Thus, it can be concluded that DBUS-based e-modules with book creator help can be implemented in learning.